Women's Role in Overcoming Nature Exploitation in Disney Movie Frozen II - Artanti Eka Ellasari Putri; Pratiwi Retnaningdyah (Humanitatis : Journal of Language and Literature, 2021)
The purpose of this paper is to analyze the interrelation between women and nature in an animation movie produced by Walt Disney and directed by Chris Buck and Jennifer Lee. The study aims at examining the relationship between women and nature in Walt Disney’s Movie Frozen II (2019), with a special focus on the destruction of nature that occurs in the movie and the role of female characters in repairing the environmental damage. Moreover, Gaard’s theory of Ecofeminism serves as the theoretical framework upon which women and nature relations are examined within the gender and ecological contexts. The study shows that there are environmental issues in the movie as a result of the dominant patriarchal system in which the king is considered as a leader of everything and everyone must obey the King's orders. Furthermore, the study shows that Elsa and Anna have the feminine values to overcoming the existing natural destruction. The results of this study reveal that women can be a leader and also the female character in this movie have feminine values to repair the existing natural destruction and maintaining the nature by reconciling with the 4 supernatural spirits. Hence, the study highlights the domination of women, the role of gender, and the ecological aspects in Frozen II movies that have not been fully explored previously.